Comportamentos pró-sociais em crianças com deficiência mental - Turini, Flávia Almeida (2006)
The pro social behaviors (PSB) are voluntary actions with the aim of benefiting another individual. This study identified the PBS in 12 children with mental retardation, 6 boys and 6 girls with a mean age of 11 years and 3 months (10-12 years) who attend from first to forth grade at two public schools in Vitória, ES. The participants were observed 5 minutes during 6 school breaks (30 minutes each). The analysis categories were: activities related to the object, place or privilege: Helping; Empathy and Cooperation. All the participants PSB were assessed involving PSB with adults, schoolmate with mental disability and schoolmate with typical development (TD) and the PSB only with schoolmate with TD. In both, there was a correlation between producing PSB and being benefited from these behaviors. The PSB added up 216; 144 were displayed by girls and 72 by boys. In the PSB with schoolmate with TD, 149 PSB occurred. The girls displayed 95 and the boys 54. However, there weren t statistic difference between boys and girls in the PSB and the analysis categories. Both boys and girls showed more behaviors in the Empathy category. Most of PSB did not involve requesting and all the consequent events came from a positive source. The girls addressed the PSB to other girls and the boys to other boys as well. The PSB were good indicators of these students social inclusion in school since most of children from this sample had a net of integration with peers with typical development.